2004
DOI: 10.1007/s11664-004-0060-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth of thick CdTe epilayers on GaAs substrates and evaluation of CdTe/n+-GaAs heterojunction diodes for an X-ray imaging detector

Abstract: The growth characteristics of thick (100) CdTe epitaxial layers of a thickness up to 200 µm on a (100) GaAs substrate in a metal-organic vapor-phase epitaxy (MOVPE) system and fabrication of CdTe/n ϩ -GaAs heterojunction diodes for their possible applications in low-energy x-ray imaging detectors are reported. The grown epilayers were of high structural quality as revealed from the x-ray double-crystal rocking curve (DCRC) analysis, where the full-width at half-maximum (FWHM) values of the (400) diffraction pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…[4][5][6] We have previously reported on the growth of CdTe layers on GaAs substrates and development of nuclear radiation detectors based on CdTe/n 1 -GaAs heterojunction diodes. 5,6 Although the nuclear radiation detection property of this heterojunction diode was successfully confirmed, in order to improve detector performance further and to achieve an even larger area, the Si substrate is considered to be more favorable than the GaAs substrates.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] We have previously reported on the growth of CdTe layers on GaAs substrates and development of nuclear radiation detectors based on CdTe/n 1 -GaAs heterojunction diodes. 5,6 Although the nuclear radiation detection property of this heterojunction diode was successfully confirmed, in order to improve detector performance further and to achieve an even larger area, the Si substrate is considered to be more favorable than the GaAs substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The details about the CdTe growth on the GaAs substrates and their characterization are reported elsewhere. [13][14][15] In order to improve the heterojunction property, a 2-5-µm-thick iodinedoped n-CdTe buffer layer was first grown at a low substrate temperature of 350°C, and was followed by the undoped p-like thick layer growth. The buffer layer has a room-temperature electron concentration of 10 16 -10 17 cm Ϫ3 .…”
Section: Detector Fabricationmentioning
confidence: 99%
“…We have previously reported on the successful growth of thick (up to 200 µm) and highquality CdTe epilayers on the GaAs substrates, and presented our efforts on detector development, which were based on CdTe/n ϩ -GaAs heterojunction diodes. 13,14 In spite of achieving a good diode property, the charge transport property of those diodes was rather poor, and it was not possible to obtain energy information of incident nuclear radiation. It was considered that the interface defect states at the junction as well as defect states in the CdTe layers possibly introduced due to the Ga diffusion were responsible for the poor transport property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on the detector fabrication have been reported in recent years. [1][2][3] One problem of the detector fabrication is formation of deep isolation trenches, which CdTe and HgCdTe pixel detectors require. In order to form deep isolation trenches, a high-speed etching technique is required.…”
Section: Introductionmentioning
confidence: 99%